<semantics>L1</semantics> Adaptive Control for Small-Scale Unmanned Helicopters: Enhancing Speed Regulation - Giulia Bertolani; Andrea Dan Ryals; Emanuele Luigi de Angelis; Lorenzo Pollini; Fabrizio Giulietti (Drones)
This paper focuses on the application of <semantics>L1</semantics> adaptive control to the speed autopilot loop of small-scale unmanned helicopters. The <semantics>L1</semantics> adaptive control technique is investigated for its potential to provide reliable speed control, particularly in handling external disturbances and model uncertainties. Although <semantics>L1</semantics> adaptive control has been widely studied, its application to small-scale unmanned helicopters remains relatively unexplored. Through numerical simulations and a preliminary experimental test campaign conducted on a small rotary-wing platform, this paper contributes to validating <semantics>L1</semantics> adaptive control as a promising solution for speed regulation in unmanned helicopter platforms.